The role of self-perceived academic competence in children with childhood-onset fluency disorder. (October 2022) - Nousia, Anastasia; Martzoukou, Maria; Siafaka, Vassiliki
The aim of the present study was to investigate the five different components of self-perception (academic competence, social acceptance, athletic competence, physical appearance and school behavior), and to identify the dimensions that affect self-esteem in children with Childhood onset Fluency Disorder (CoFD). The study sample consisted of thirty children with CoFD and, as controls, thirty children without CoFD, aged from 9 to 11;7 years old. The following instruments were used: (1) the Greek version of Self-Perception Profile for Children (SPPC), (2) the "Children's Phonetic and Phonological development assessment" and, (3) a demographic characteristics form. Results revealed that while children with CoFD did report lower perceived academic competence than did those of the control group, and their academic competence self-perception shaped both their self-esteem and their school behavior self-perception. Moreover, academic competence self-perception was found to mediate in the relationship between CoFD, self-esteem and school behavior self-perception. Perceived academic competence in children with CoFD is linked to self-esteem and perceived school behavior, and this may impact on their relationships, emotional health and overall well-being. Health professionals should become able to estimate coexisting psychological difficulties and negative behaviors of parents or teachers that may affect the children's self-esteem. Furthermore, they should be able to suggest targeted psychological interventions for children and parents, while in the same frame teachers need to be properly trained about the management of stuttering in the classroom. The role of the speech therapist in the school context for in-service provision of information is therefore considered to be of paramount importance.